2013
DOI: 10.1186/1824-7288-39-7
|View full text |Cite
|
Sign up to set email alerts
|

The origins of health and disease: the influence of maternal diseases and lifestyle during gestation

Abstract: According to the Barker hypothesis, the period of pregnancy and the intrauterine environment are crucial to the tendency to develop diseases like hypertension, diabetes, coronary heart disease, metabolic disorders, pulmonary, renal and mental illnesses. The external environment affects the development of a particular phenotype suitable for an environment with characteristics that closely resemble intrauterine conditions. If the extra-uterine environment differs greatly from the intra-uterine one, the fetus is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 118 publications
3
58
1
1
Order By: Relevance
“…Verhaak) was involved in the final discussion for an independent third opinion, which resulted in final quality ratings. Based on these ratings, the studies were grouped into low-quality (0-3), moderate-quality (4-6) and high-quality (7)(8) studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Verhaak) was involved in the final discussion for an independent third opinion, which resulted in final quality ratings. Based on these ratings, the studies were grouped into low-quality (0-3), moderate-quality (4-6) and high-quality (7)(8) studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Although previous data demonstrated that genetic factors contributed to gestational length and risk of preterm birth (12), non-genetic factors may also influence oxidative stress and redox system imbalances in the maternal-foetal intrauterine compartment (13). Maternal lifestyle (14) and health status, including diseases with onset prior to or during pregnancy (15), may influence oxidative stress and affect the apoptotic pathway leading to at-term birth or sPTB, both of which also appear consequent to a mechanism involving genetic and non-genetic factors, which may modulate the oxidative stress-induced apoptosis.…”
Section: Induction Of the Apoptotic Pathway By Oxidative Stress Inmentioning
confidence: 96%
“…In 1992, David Barker hypothesized that the period of pregnancy and the intrauterine environment have a profound impact on risk of developing diseases like hypertension; diabetes; cardiac, pulmonary, and renal diseases; and mental illness (Capra et al 2013). Intrauterine environment and early postnatal life are now generally accepted as important factors that may lead to increased risk for disease in adulthood (Hofman et al 2004).…”
Section: The Impact Of Fetal Environment and Prematurity On Adult Heamentioning
confidence: 99%